2018
DOI: 10.1097/nna.0000000000000695
|View full text |Cite
|
Sign up to set email alerts
|

The Intergenerational Impact of Management Relations on Nurse Career Satisfaction and Patient Care

Abstract: Objective This article provides insights into the role of management relations on nurses’ career satisfaction across different career stages. Background Managers and positive relations with staff are critical to improving job satisfaction, career development, and retention for new graduates to mid- to late-career nurses. Methods Using a descriptive qualitative approach, we conducted a thematic analysis of 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 14 publications
1
17
0
1
Order By: Relevance
“…Previous studies have pointed to the value of senior nurses engaging novice nurses during their transition period, to provide relevant professional support and discuss issues novice nurses may encounter [15]. Indeed, it has been found that when young novice nurses receive support and interpersonal care, this can have long-term and positive impacts on working relationships [46]. Future research may examine what inhibits this form of communication between senior and novice nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have pointed to the value of senior nurses engaging novice nurses during their transition period, to provide relevant professional support and discuss issues novice nurses may encounter [15]. Indeed, it has been found that when young novice nurses receive support and interpersonal care, this can have long-term and positive impacts on working relationships [46]. Future research may examine what inhibits this form of communication between senior and novice nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Rev enferm UERJ, Rio de Janeiro, 2021; 29:e61186 p.5 dano é prejudicial para qualidade de vida do profissional e pode interferir na sua atuação. O não desenvolvimento, pelos enfermeiros, de atividades condizentes com aquilo que planejaram executar na sua profissão pode dificultar o desempenho das funções e um trabalho que leva o profissional ao adoecimento 20 .…”
Section: Discussionunclassified
“…Previous research showed that nurses value managers who can empower them to act on their expert judgment and provide frequent and meaningful feedback, and that the relationship with the manager is a factor for job satisfaction (Force, 2005; Olson‐Sitki et al, 2012). Price et al (2018) highlighted relationships as a part of managers’ daily work and reported that nurses considered the effect of positive management relationships on job satisfaction and the provision of quality patient care to be important. The role of team members in competence development has been described in several studies (Ahlstedt et al, 2019; Huston et al, 2018; Leggat, 2007).…”
Section: Discussionmentioning
confidence: 99%